1993
DOI: 10.1577/1548-8675(1993)013<0160:aoshta>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Stocking Hatchery Trout: A Wyoming Perspective

Abstract: We evaluated Wyoming Game and Fish Department (WGFD) file information to determine the species of trout raised, the number of catchable-and subcatchable-size trout stocked, the return rate of stocked fish to the creel, reasons for variability of return rates, and the direct cost associated with stocking trout. About 8.9 million trout were planted yearly from 11 WGFD hatcheries during 1987-1990; 86% were of subcatchable size (<8.25 in) and the rest were of catchable size (^8.25 in). Rainbow trout Oncorhynchus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 13 publications
6
69
2
Order By: Relevance
“…For example, it has been suggested that stocking trout in the fall increases survival because warm-and cool-water predators such as largemouth bass and walleye become less active (Wiley et al 1993, Yule et al 2000. However, we observed largemouth bass predation on rainbow trout to occur only during the fall due to spatial habitat overlap and stocking of vulnerable sized fish.…”
Section: Discussioncontrasting
confidence: 55%
“…For example, it has been suggested that stocking trout in the fall increases survival because warm-and cool-water predators such as largemouth bass and walleye become less active (Wiley et al 1993, Yule et al 2000. However, we observed largemouth bass predation on rainbow trout to occur only during the fall due to spatial habitat overlap and stocking of vulnerable sized fish.…”
Section: Discussioncontrasting
confidence: 55%
“…Wiley (2003) reported that average costs for stocking subcatchable trout in headwater lakes in Wyoming were relatively low, about $260 per lake. This estimate is for the short-run marginal cost of producing fish (i.e., limited to costs associated with operating hatcheries and distributing fish), which in Wyoming was $0.13 per subcatchable and $0.68 per catchable trout (1990 dollars; Wiley et al 1993). Johnson et al (1995) and Loomis and Fix (1999) derived similar estimates-$0.57 (1988 dollars) and $1.11 (1992 dollars)-to produce a catchable trout in Colorado state hatcheries.…”
Section: Photos: Davids Pilliodmentioning
confidence: 98%
“…Pister (2001) issued a challenge to fisheries managers to assess the costs and benefits of headwater fisheries in wilderness areas, arguing that it was unlikely that stocking was cost-effective. Wiley et al (1993) stated, "Trout stocking programs can generate further pernicious demand, resulting in increased and unnecessary dependence on hatchery trout, because people come to expect planted trout. Successful management programs address public interests as well as the biology of the fish so than angler expectations are at least partly met by foresighted management agencies."…”
Section: Photos: Davids Pilliodmentioning
confidence: 99%
See 1 more Smart Citation
“…An evaluation of stocking rainbow trout at various sizes in Seminoe Reservoir, Wyoming, found an increase in creel return rates for larger fish (≥210 mm TL) because smaller fish (<210 mm TL) were susceptible to predation by walleye (Wiley et al 1993). Yule et al (2000) suggested that in the presence of established walleye populations, rainbow trout needed to be stocked at sizes >208 mm TL to maintain viable rainbow trout fisheries.…”
Section: Management Implicationsmentioning
confidence: 99%